Silicone oil impregnated nano silica modified glass surface and influence of environmental dust particles on optical transmittance. Issue 47 (7th June 2017) - Yilbas, Bekir Sami; Yousaf, Muhammad Rizwan; Al-Sharafi, Abdullah; Ali, Haider; Al-Sulaiman, Fahad; Abu-Dheir, Numan; Khaled, Mazen; Al-Aqeeli, Nasser
Abstract : The behavior of environmental dust particles on a silicone oil impregnated glass surface is examined in relation to optical transparent surfaces for self-cleaning applications. Abstract : The behavior of environmental dust particles on a silicone oil impregnated glass surface is examined in relation to optical transparent surfaces for self-cleaning applications. The characteristics of environmental dust, collected in the local area, are analyzed using analytical tools. Functional silica particles are synthesized and deposited on the glass surface prior to silicone oil impregnation. Optical properties of functionalized silica particle deposited glass surfaces are examined prior to and after oil impregnation. Further tests are conducted in the open environment to assess dust settlement in silicone oil and dust particle sedimentation on the glass surface. It is found that dust particles have various sizes and shapes, and they are composed of various metallic, alkaline, and alkaline earth metallic compounds. The average size of the dust particles is of the order of 1.2 μm. Silicone oil impregnation considerably improves the optical transmittance of functionalized silica particle deposited glass. A high spreading rate gives rise to a cloaking of dust particles on the oil surface, which gradually reduces the surface tension force and modifies the vertical force balance. Consequently, dust particles immerse into the oil film and sediment on the glass surface. This, in turn, lowers the optical transmittance of the oil impregnated glass surfaces greatly.